(untitled) (Canadian Allergy & Immunology Today, 2023)
Born in 470 BC, Socrates was a classical Greek philosopher regarded as the first moral philosopher and founder of Western ethical thought. According to Plato, Socrates’ contemporaries called him atopos, typically translated as strange or absurd, but meaning out of place, without a place, or placeless for his nuanced thoughts and ideas.1 2300 years later, the term atopy describes the atopic family of diseases: atopic dermatitis (AD), allergic asthma (AA), hay fever, food allergy and allergic rhinitis (AR). By the end of the 19th century, scientists noticed that immune responses cause adverse reactions in specific instances. The concept that immune responses cause the disease seemed irreconcilable with the protective function of immunity; consequently, they were grouped as hypersensitivity reactions. Certain human illnesses belonging to the hypersensitivities group, now known as allergies, were ultimately classified in the early 20th century.